Effects of conventional and organic feed on the mineral composition of cultured European sea bass (Dicentrarchus labrax). (25th June 2016) - Siano, F.; Bilotto, S.; Nazzaro, M.; Russo, G.L.; Di Stasio, M.; Volpe, M.G.
Abstract: European sea bass ( Dicentrarchus labrax ) is a widely consumed marine fish in Mediterranean areas, and different farming techniques are applied for fish culturing to satisfy the growing demand for seafood. The aim of this study was to investigate the effects of conventional and organic feed on the quality of cultured European sea bass ( Dicentrarchus labrax ) collected during the growth period. The concentrations of ash, moisture, essential macro‐elements (Ca, K, Mg, Na and P), micro‐elements (Co, Cr, Cu, Fe, Mn, Ni and Zn) and toxic elements (As, Cd, and Pb) were determined in feeds and in fillets of cultured fish. The results were compared to those obtained from wild sea bass. Results showed that the differences between organic diet‐fed and conventional diet‐fed sea basses varied in relation to the specific element measured and the growth period. The former showed higher concentration of Fe, Mg and Cr, and lower Na content. The amount of P, Na, Fe, Cu and Cr in wild sea bass was significantly ( P  ≤ 0.05) higher than that found in farmed fish. The levels of toxic elements in cultured sea bass were always within the allowed limit for fishery products. Wild samples had significantly ( P  ≤ 0.05) higher content of arsenic and lead than farmed sea bass. Cultured fish represent a valuable dietary source of essential macro‐ and micro‐elements. Controlled rearing systems and feedings were related to a decrease in the presence of some toxic metals in cultured fish compared with wild fish.